Common genetic variants in platelet surface receptors and its association with ischemic stroke. (June 2016) - Milanowski, Lukasz; Pordzik, Justyna; Janicki, Piotr K; Postula, Marek
Ischemic stroke has been named one of the leading causes of death worldwide. Whereas numerous biological mechanisms and molecules were found to be associated with stroke, platelets are particularly contributive to its pathogenesis. Recent data indicate considerable variability in platelet phenotype which accounts for differences in platelet surface receptor function, count and reactivity. These features collectively influence both the events leading to a disease and effectiveness of antiplatelet therapies. Consequently, genetic variants predisposing to cerebrovascular diseases can be sequenced using a wide array of techniques and become a useful tool in clinical setting. In this review, we provide an outline of common platelet polymorphisms that impose risk on ischemic stroke development and should be evaluated as targets to improve treatment. As study results are often inconsistent, partly due to differences in demographic characteristics between study populations and the fact that the functional impact of these variants has been relatively small, we conclude that both rare, low-frequency and common variants might account for genetic contribution on abnormal platelet response to antiplatelet drugs.